Аудиоподдержка контента электронного курса; Дистанционное и виртуальное обучение; № 4 (106) - Котов С. О. Сергей Олегович; Лобаненко О. Б. Ольга Борисовна; Решетникова С. Л. Светлана Леонидовна; Ситникова О. В. Оксана Валерьевна (Виртуальные технологии, 2016)
Заглавие с экрана